Parental Attachment in Generation Z Adolescents: Comparison in Matrilineal and Patrilineal Kinship Systems in Indonesia - Arifatus Sholekhah; Pradytia Putri Pertiwi (Gadjah Mada Journal of Psychology)
Parental attachment has an immense influence on adolescent development, including in Generation Z. Some factors can affect attachment development, such as social environment and culture. This study aimed to compare attachment patterns between Generation Z adolescents from matrilineal and patrilineal backgrounds in Indonesia. The parental attachment was measured using the Indonesian version of the Inventory of Parent Peer Attachment-Revised (IPPA-R). Participants in this study were 206 adolescents, with Batak (n= 69) and Minangkabau (n=134) ethnic backgrounds. Data analyses used were Mann-Whitney U and Wilcoxon rank-sum test. This study showed no difference in parental attachment between the two groups, indicating that there is a shift in parental attachment levels in Indonesia. Trust, communication, and alienation could predict preferred attachment figures for the matrilineal group. Meanwhile, the preferred attachment figure in the patrilineal group was predicted by trust and communication. This research could help parents understand the importance of communication, trust, and alienation and their relations with parental attachment level, especially in Generation Z with Minangkabau and Batak cultural backgrounds.